Is violence used to promote Mixed Martial Arts?. Issue 4 (1st July 2015) - Greenwell, T. Christopher; Thorn, Dustin; Simmons, Jason
Abstract : This study examines how Mixed Martial Arts (MMA) events are marketed in order to understand the role of violence in promoting events. Researchers examined 134 pieces of promotional artwork and 57 promotional news releases by MMA organisations across North America, Asia and Europe and found that 18 (13.4%) pieces of promotional artwork used violent text or imagery. Violent text was found in 12 (21%) of the 57 news releases. Violence was typically limited to smaller or European organisations. Results illustrate an evolution of the sport, suggesting violence may no longer be necessary to promote events.